2017
DOI: 10.1186/s12985-017-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Geraniin extracted from the rind of Nephelium lappaceum binds to dengue virus type-2 envelope protein and inhibits early stage of virus replication

Abstract: BackgroundThe rapid rise and spread in dengue cases, together with the unavailability of safe vaccines and effective antiviral drugs, warrant the need to discover and develop novel anti-dengue treatments. In this study the antiviral activity of geraniin, extracted from the rind of Nephelium lappaceum, against dengue virus type-2 (DENV-2) was investigated.MethodsGeraniin was prepared from Nephelium lappaceum rind by reverse phase C-18 column chromatography. Cytotoxicity of geraniin towards Vero cells was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…Compounds with antiviral properties against dengue serve as a promising alternative to dengue therapy. In our previous in vitro study, we showed that geraniin inhibits early stage of DENV-2 replication, particularly the attachment process, by binding to the viral E protein, specifically at the Domain III region [28]. In our current study, we further prove the inhibitory potential of geraniin by quantifying the DNA production in geraniin treated-infected Vero cells.…”
Section: Discussionsupporting
confidence: 58%
“…Compounds with antiviral properties against dengue serve as a promising alternative to dengue therapy. In our previous in vitro study, we showed that geraniin inhibits early stage of DENV-2 replication, particularly the attachment process, by binding to the viral E protein, specifically at the Domain III region [28]. In our current study, we further prove the inhibitory potential of geraniin by quantifying the DNA production in geraniin treated-infected Vero cells.…”
Section: Discussionsupporting
confidence: 58%
“…The objectives of this study were to investigate the cytotoxicity effect of betacyanin fractions from red pitahaya and red spinach on Vero cells, followed by investigating the antiviral activity of betacyanin fractions against dengue virus serotype 2 (DENV-2) via virus yield inhibition assay and virucidal assay. Only DENV-2 was investigated because it is the most lethal among four serotypes [ 3 ] and it has low efficacy for Dengvaxia vaccine especially for seronegative individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…GN is one of the ellagitannins which contain up to 10% of GH. GN is present in different parts of various types of plants and exhibits antiviral activity against HSV-1 and -2 30 , HIV-1 38 , HBV 39 , human enterovirus 71, and dengue virus type-2 40 . However, to date, there has been no report on the specific uses of GN in the inhibition of the NA activity of influenza viruses.…”
Section: Discussionmentioning
confidence: 99%